THE IMPACT OF TAHAJUD PRAYER IMPLEMENTATION ON THE DISCIPLINE OF FEMALE SANTRI AT PONDOK PESANTREN AL-AMANAH - Nur Dila Agustina; Abdul Rahim; Safaruddin Yahya (Dirasah: Jurnal Pendidikan Islam, 2025)
This study aims to analyze the effect of performing Salat Tahajud on the level of discipline among students at Al-Amanah Islamic Boarding School. This research uses a quantitative method with an associative approach, which aims to determine the influence of the independent variable (the practice of Salat Tahajud) on the dependent variable (student discipline). The population in this study consists of all female students in the 5th grade of KMI at Al-Amanah Islamic Boarding School, using purposive sampling with a total sample of 35 students who regularly perform Tahajud prayer. The data collection techniques used in this study include questionnaires, observations, and documentation. The results of the study indicate that: (1) the level of influence of Tahajud prayer practice among students at Al-Amanah Islamic Boarding School has an average score of 41.43, categorized as moderate; (2) the level of disciplinary behavior among students at Al-Amanah Islamic Boarding School has an average score of 39.42, also categorized as moderate; (3) there is a significant positive influence of Tahajud prayer practice on students' disciplinary behavior at Al-Amanah Islamic Boarding School. The influence of Tahajud prayer practice is 32%, while the remaining 68% is influenced by other factors